MODAL SIMBOLIS DAN KEKERASAN SIMBOLIK: KOMERSIALISASI ISLAMOPHOBIA OLEH AKUN INSTAGRAM @PERMADIAKTIVIS2 - Rosadi, Didi; Swarnawati, Aminah; Sanjaya, Makroen (Universitas Gunadarma, 2025)
This study aims to analyze the phenomenon of commercialization of Islamophobia carried out by the Instagram account @permadiaktivis2 using the symbolic capital and symbolic violence analysis approaches. Through qualitative and ethnographic methods, this study observes social interactions and cultural practices that develop around the account. Data were obtained through participant observation, in-depth interviews, and text analysis of the content, comments, and hashtags used. The research findings show that the @permadiaktivis2 account utilizes symbolic capital to build identity and authority among its followers and implements symbolic violence through symbols and narratives that demean Muslims. In addition, this account also posts provocative content to attract attention and increase interaction, which supports commercialization efforts through advertising, sponsorships, and Instagram's monetization features. This phenomenon exacerbates stereotypes and discrimination against Muslims and emphasizes the importance of creating an inclusive and hate-free social media environment. This study provides an understanding of how social media can be used to spread and commercialize Islamophobia, as well as its impact on public perceptions of Islam.